PREVENTION AND TREATMENT OF POSTPARTUM HEMORRHAGE: A LITERATURE REVIEW - Yohana Rita Bitbit; Mardiana Ahmad; Isharyah Sunarno (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: The main cause of morbidity and maternal mortality is hemorrhage postpartum, with an increasing incidence around the world. Various risk factors for postpartum bleeding are expected to be an effective treatment by health professionals and have a role as advocates, collaborators, educators, service providers, and as researchers must have the latest knowledge in providing optimal and comprehensive care. Objectives: This study aimed to find out the prevention and treatment of hemorrhage postpartum. Design: This study design is a systematic review to search and review articles from database and the descriptive theory. Data Sources: Search scientific articles using the Mendeley application by entering the keywords